2020
DOI: 10.1007/s10291-020-01043-5
|View full text |Cite
|
Sign up to set email alerts
|

GLONASS FDMA data for RTK positioning: a five-system analysis

Abstract: The use of the GLONASS legacy signals for real-time kinematic positioning is considered. Due to the FDMA multiplexing scheme, the conventional CDMA observation model has to be modified to restore the integer estimability of the ambiguities. This modification has a strong impact on positioning capabilities. In particular, the ambiguity resolution performance of this model is clearly weaker than for CDMA systems, so that fast and reliable full ambiguity resolution is usually not feasible for standalone GLONASS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…This fast convergence to the centimeter level is of great importance, as it implies that a single-receiver user can achieve such rapid positioning results without the use of a precise ionosphere model and, more importantly, without the need for a dense reference network to provide regional atmospheric corrections. With the above real data results, we believe that more studies can be considered for achieving near-instantaneous PPP-RTK positioning by incorporating GLONASS, BeiDou and QZSS data, similar to the five-system analysis of Brack et al [14].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This fast convergence to the centimeter level is of great importance, as it implies that a single-receiver user can achieve such rapid positioning results without the use of a precise ionosphere model and, more importantly, without the need for a dense reference network to provide regional atmospheric corrections. With the above real data results, we believe that more studies can be considered for achieving near-instantaneous PPP-RTK positioning by incorporating GLONASS, BeiDou and QZSS data, similar to the five-system analysis of Brack et al [14].…”
Section: Discussionmentioning
confidence: 72%
“…With the current proliferation of GNSS systems, the availability of more satellites paves the way for further improvements to PPP-RTK ambiguity resolution and positioning based on the ionosphere-float model, i.e., the model which parameterizes the ionospheric delays as completely unknown parameters. In general, combining systems brings an improved satellite geometry that translates into reduced convergence times, as was demonstrated for GPS and BeiDou [7], GPS and Galileo [8,9], three-system GPS, Galileo and BeiDou [10,11], four-system GPS, Galileo, BeiDou and GLONASS [12,13], and five-system GPS, Galileo, BeiDou, GLONASS and QZSS [14].…”
Section: Introductionmentioning
confidence: 96%
“…They showed that for both standalone GLO-NASS and combined GLONASS+GPS, faster convergence time and more precise positioning solutions can be obtained once the GLONASS FDMA integer-estimable ambiguities are fixed. In Brack (2020) and Brack et al (2020), the new FDMA model was analyzed for multi-GNSS RTK positioning, considering short to long baselines. They proposed a partial ambiguity resolution approach with which the inclusion of the GLONASS integer-estimable FDMA model in multi-GNSS RTK positioning was beneficial under all considered cases.…”
Section: Introductionmentioning
confidence: 99%
“…Ionosphere-weighted GNSS parameter estimation is a popular and very flexible technique for strengthening estimator performance in the presence of ionospheric model delays. It is used in a wide variety of GNSS applications, ranging from the use of external ionospheric models (Schaer 1999;Memarzadeh 2009;Feltens et al 2011) to the incorporation of ionospheric corrections from reference networks, for instance for PPP or PPP-RTK (Odijk 2000;Paziewski 2016;Tomaszewski et al 2020;Teunissen 2021), and the strengthening of medium to long baseline models (Teunissen 1997;Bock 1998;Odolinski and Teunissen 2017;Brack et al 2021). However, no clear and provable rules have been established that specify the needed weighting in dependence on ionospheric circumstances.…”
Section: Introductionmentioning
confidence: 99%